Pin number detection from mobile phone scratch card using OCR on android platform and build an application for balance recharge - Khan, Md Nazrul Hasan; Siddiqui, Faizan; Das, Amit (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.